Associations of multi-decadal sea-surface temperature variability with US drought - McCabe, Gregory J.; Betancourt, Julio L.; Palecki, Michael A.; Hidalgo León, Hugo G.; Gray, Stephen T. (Quaternary International, 2008)
Recent research suggests a link between drought occurrence in the conterminous United States (US) and sea surface temperature (SST) variability in both the tropical Pacific and North Atlantic Oceans on decadal to multidecadal (D2M) time scales. Results show that the Atlantic Multidecadal Oscillation (AMO) is the most consistent indicator of D2M drought variability in the conterminous US during the 20th century, but during the 19th century the tropical Pacific is a more consistent indicator of D2 M drought. The interaction between El Niño-Southern Oscillation (ENSO) and the AMO explain a large part of the D2M drought variability in the conterminous US. More modeling studies are needed to reveal possible mechanisms linking low-frequency ENSO variability and the AMO with drought in the conterminous US. National Oceanographic and Atmospheric Administration//NOAA/Estados Unidos Universidad de Costa Rica//UCR/Costa Rica UCR::Vicerrectoría de Investigación::Unidades de Investigación::Ciencias Básicas::Centro de Investigaciones Geofísicas (CIGEFI)